Socio-Economic Effects of Demolishing Squatter Settlements in Noorpur Shahan, Islamabad: An ESG Perspective - Khan, Kamran (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
This study investigates the socio-economic consequences of demolishing squatter settlements in Noorpur Shahan (originally Chorpur), Islamabad, through an Environmental, Social, and Governance (ESG) lens. Using primary qualitative methods, including field visits, structured interviews with affected residents, and direct observations, the research highlights how forced evictions disrupt livelihoods, income, social networks, and psychological well-being. Despite limited environmental or governance benefits, the demolitions reflect gaps in policy planning and a neglect of social considerations. The findings emphasize the need for inclusive resettlement strategies, social protection measures, and community engagement in urban development policies to mitigate adverse impacts on marginalized populations.